Nephroprotective Role of Combined Sitagliptin and Oleuropein in Cisplatin-Induced Acute Kidney Injury: Regulation of SDF-1α/Nrf2/ HO-1 Axis and Autophagy - Mohamed Bassiony; Nesreen O Omar; Amira M Badr; Nadia M Hamdy; Eman F Sanad (Ain Shams University, 2021)
Background: Accumulating evidence proves that cisplatin, a widely used anticancer, causes acute kidney injury (AKI). Sitagliptin (Sita), a dipeptidyl peptidase-4 (DPP4) inhibitor, is a hypoglycemic agent that can promote tissue angiogenesis and cell survival. However, little is known about the nephroprotective effect of Sita in cisplatin-induced AKI especially its effect on SDF-1α, usually degraded by DPP4. Meanwhile, the olive oil component oleuropein (Ole) activates Nrf2/heme oxygenase-1 (HO-1) axis, which ultimately leads to SDF-1α activation. Herein, we studied the nephroprotective effects of combined Sita and Ole on oxidative stress and autophagy through SDF-1α/Nrf2/ HO-1 axis in cisplatin-induced AKI in rats. Methods: AKI was induced in vivo through single IP injection of cisplatin (7 mg/kg), while Sita (10 mg/kg) and Ole (16 mg/kg) were given separately and in combination for 7 days prior and 5 days after cisplatin injection. AKI was assessed through histopathological examination, measurement of serum creatinine and urea. Also, serum GLP-1, serum and kidney SDF-1α levels were measured by ELISA. LC3-II, P62, HO-1, Nrf2, and caspase-3 were investigated by western blotting. Results: Sita and Ole monotherapy and in combination accelerated kidney recovery as they suppress serum SDF-1α, serum BUN, creatinine and renal histopathological features. Each of Sita and Ole enhanced Nrf2/HO-1axis in renal tissues while only Sita enhanced renal SDF-1α. Sita and Ole monotherapy showed incompetent autophagy where the late steps of autophagy were incomplete. Combined treatment enhanced SDF-1α in kidney tissue which showed recovery through autophagy process. Conclusion: Sita and Ole show promising nephroprotective effects in cisplatin-induced AKI